2011
DOI: 10.1104/pp.111.174524
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Grain Development Is Characterized by Remarkable Trehalose 6-Phosphate Accumulation Pregrain Filling: Tissue Distribution and Relationship to SNF1-Related Protein Kinase1 Activity    

Abstract: Trehalose 6-phosphate (T6P) is a sugar signal that regulates metabolism, growth, and development and inhibits the central regulatory SNF1-related protein kinase1 (SnRK1; AKIN10/AKIN11). To better understand the mechanism in wheat (Triticum aestivum) grain, we analyze T6P content and SnRK1 activities. T6P levels changed 178-fold 1 to 45 d after anthesis (DAA), correlating with sucrose content. T6P ranged from 78 nmol g 21 fresh weight (FW) pregrain filling, around 100-fold higher than previously reported in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(152 citation statements)
references
References 39 publications
8
140
1
1
Order By: Relevance
“…Inhibition of SnRK1 by T6P results in up-regulation of genes involved in biosynthetic processes and growth (Zhang et al, 2009;Paul et al, 2010;Debast et al, 2011;Martínez-Barajas et al, 2011;), whereas low T6P and active SnRK1 result in upregulation of plant stress responses and catabolism rather than anabolism (Baena-González et al, 2007;Zhang et al, 2009;Debast et al, 2011). T6P contents are related to those of Suc in plants (Lunn et al, 2006;Martínez-Barajas et al, 2011). Accordingly, a model has been developed where T6P elicits changes in gene expression through regulation of SnRK1 promoting growth in relation to Suc supply.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of SnRK1 by T6P results in up-regulation of genes involved in biosynthetic processes and growth (Zhang et al, 2009;Paul et al, 2010;Debast et al, 2011;Martínez-Barajas et al, 2011;), whereas low T6P and active SnRK1 result in upregulation of plant stress responses and catabolism rather than anabolism (Baena-González et al, 2007;Zhang et al, 2009;Debast et al, 2011). T6P contents are related to those of Suc in plants (Lunn et al, 2006;Martínez-Barajas et al, 2011). Accordingly, a model has been developed where T6P elicits changes in gene expression through regulation of SnRK1 promoting growth in relation to Suc supply.…”
Section: Discussionmentioning
confidence: 99%
“…It could also represent a possible famine threshold level of Suc above which growth is induced. While a strong relationship is seen between Suc and T6P, other studies (Martínez-Barajas et al, 2011) in an analysis of wheat (Triticum aestivum) grain have shown a relationship with catabolites of Suc and T6P, including Glc. To test the specificity of the interrelationship between Suc and T6P, feeding of 0.5% (w/v) Glc was performed.…”
Section: Suc Gmentioning
confidence: 94%
See 1 more Smart Citation
“…Spraying of wheat plants with compounds that release T6P upon exposure to sunlight led to increased grain yield due to the formation of larger grains with higher starch content (Griffiths et al, 2016b). Earlier work had shown that T6P naturally accumulates in wheat grains to previously unreported levels before grain filling (Martínez-Barajas et al, 2011). Interestingly, T6P content was low in the embryonic and maternal tissues and accumulated almost exclusively in the endosperm, although at later stages it may also be required in the embryo itself.…”
Section: Seed Developmentmentioning
confidence: 99%
“…SnRK1 thus has a positive effect on seed maturation and storage protein synthesis, which is opposite to its characteristic role in starvation signaling and activation of catabolic pathways (Baena-González and Sheen, 2008). In developing wheat grains, in vitro SnRK1 activity was reported in the embryo and endosperm, which together with low T6P in the embryo may support high in vivo SnRK1 activity for embryo maturation (Martínez-Barajas et al, 2011). The C/S1 bZIP transcription factors, in particular, bZIP53, which is expressed late during seed development, have also been proposed to be involved in storage protein synthesis and seed maturation Alonso et al, 2009;Restovic et al, 2017).…”
Section: Seed Developmentmentioning
confidence: 99%